Description of the male of Dolomedes raptoroides Zhang, Zhu & Song, 2004 (Araneae: Lycosoidea: Pisauridae) - Da Silva, Estevam L. Cruz; Gibbons, Anne; Sierwald, Petra (Zootaxa, 2015)
Dolomedes Latreille, 1804 is the most diverse genus in Pisauridae, with 98 described species and a wide range of distribution on every continent, except Antarctica (World Spider Catalog 2014). The genus has never been comprehensively revised. Roewer’s (1955) monograph covered African species of the genus; Carico (1973) revised the Nearctic species; Vink & Dupérré 2010 revised the four Dolomedes species of New Zealand.